2015
DOI: 10.1007/978-81-322-2511-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Hydrogels for Regenerative Engineering

Abstract: Research in the field of hydrogels has been actively growing for the past couple of decades. Hydrogels are crosslinked polymers with high water content. They can be prepared from natural, synthetic, and composite polymers using different chemical and physical crosslinking methods. Hydrogels have been widely explored for the delivery of bioactive molecules, drugs, and for other therapeutic applications. Chitosan-based hydrogels have unique advantages owing to their biocompatibility, biodegradability, antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 176 publications
(209 reference statements)
0
9
0
1
Order By: Relevance
“…Hydrogels consist of insoluble polymer networks swelled in water that present advantageous viscoelastic properties [ 1 , 2 , 3 , 4 ]. Hydrogels are very interesting in biomedical applications like tissue engineering and regenerative medicine (TERM) domains [ 2 , 4 ] as well as drug delivery [ 4 ] (such as proteins [ 3 ], growth factors, antibiotics, anti-inflammatories, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels consist of insoluble polymer networks swelled in water that present advantageous viscoelastic properties [ 1 , 2 , 3 , 4 ]. Hydrogels are very interesting in biomedical applications like tissue engineering and regenerative medicine (TERM) domains [ 2 , 4 ] as well as drug delivery [ 4 ] (such as proteins [ 3 ], growth factors, antibiotics, anti-inflammatories, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are very interesting in biomedical applications like tissue engineering and regenerative medicine (TERM) domains [ 2 , 4 ] as well as drug delivery [ 4 ] (such as proteins [ 3 ], growth factors, antibiotics, anti-inflammatories, etc. [ 2 ]) due to their unique characteristics such as biocompatibility, biodegradability, ability to mimic the extracellular matrix (ECM); and their capacity for controlled release of bioactive molecules [ 1 , 2 , 5 ]. Concerning the delivery to the injury area, injectable hydrogels have gained wider appreciation with their ease of handling [ 6 ], their capacity to fill irregular tissue defects of various sizes [ 7 , 8 , 9 ], and their potential for mini-invasive surgical procedures [ 2 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan solubility depends on distribution of N-acetyl and free amino groups. Protonation of amino groups occurs at pH<6.0 due to which chitosan become soluble [ 16 ] but at basic pH protonation does not occur and pH value of ~6.5 leads to solubility and insolubility transition [ 17 ]. Recent studies revealed the conversion of chitosan to oligomers as oligomers are soluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…• Quitina y sus derivados: la quitina es el segundo biopolímero más abundante; es un polisacárido lineal compuesto por unidades de N-acetilglucosamina unidas por enlaces β-(1-4), y se encuentra en el exoesqueleto de los crustáceos, la cutícula de los artrópodos, el caparazón de los moluscos y la pared celular de algunos hongos [101] . El quitosano es un derivado de la quitina y está compuesto de cadenas de D-glucosamina y N-acetil-D-glucosamina que se distribuyen aleatoriamente [102] . Este material se ha utilizado en aplicaciones biomédicas debido a su biocompatibilidad, biodegradabilidad y baja toxicidad; adicionalmente, en el tratamiento de heridas es útil por sus propiedades antibacteriales, hemostáticas y mucoadhesivas [103] [104] , acelera el proceso de cicatrización debido a que promueve la migración de neutrófilos polimorfonucleares e induce la granulación ya que ayuda en la proliferación de fibroblastos [105] .…”
Section: Naturalesunclassified